News Text on Kompas.com Media of Covid-19 and the Underlying Conspiracy Theory: A Teun Van Dijk’s Critical Discourse Analysis - Veronika Unun Pratiwi; Nofrahadi Nofrahadi; Apri Pendri; Dina Komalasari; Sumarlam Sumarlam (Budapest International Research and Critics University, 2020)
This article critically examines the news of the coronavirus (COVID-19) pandemic in the press. This article tries to examine how the COVID-19 news is used for political and ideological purposes. To achieve this goal, an analysis was carried out on the Kompas.com Online Media newspaper on 11 June 2020 and 05 September 2020. The Van Dijk news scheme framework is used to analyze reports selected from selected topics of Covid 19. Van Dijk's news scheme is very important to analyze every news (report) whether the news is taken from news channels or newspapers and whether broadcast or printed. Based on data analysis, the article found that COVID-19 news had been politicized and used for ideological purposes. The article recommends that a pandemic should not be politicized by either the media or any party, but we must work together so that the government and media personnel are able to work effectively and deal with this long-running pandemic.